2021
DOI: 10.3389/fresc.2021.710580
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing the Family to Improve Inclusion in Childhood Disability Research and Practice

Abstract: The World Health Organization's International Classification of Functioning, Disability and Health recognizes that environmental factors impact well-being and life participation for children with disabilities. A primary environment in which children grow and learn is the family. The importance of family has long been recognized in family-centered practice and family-centered research. Although family-centered services and research have been critically explored, the concept of family has received less critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Further research is needed to determine how to implement these suggestions while still collecting usable, valid data, although research examining the use of smartphone-collected parental reports of behavior in children with autism suggested that data collection may be abbreviated without compromising study integrity. 20 Involvement of multiple caregivers/family members was also cited as key, mirroring recent work by Phoenix et al, 21 advocating for the representation of diverse family structures in research, and recognizing that caregiving roles can be uniquely dispersed in the context of supporting children with disabilities. Reciprocity describes the mutual benefit to both researchers and participants that results from effective community-based research.…”
Section: Discussionmentioning
confidence: 82%
“…Further research is needed to determine how to implement these suggestions while still collecting usable, valid data, although research examining the use of smartphone-collected parental reports of behavior in children with autism suggested that data collection may be abbreviated without compromising study integrity. 20 Involvement of multiple caregivers/family members was also cited as key, mirroring recent work by Phoenix et al, 21 advocating for the representation of diverse family structures in research, and recognizing that caregiving roles can be uniquely dispersed in the context of supporting children with disabilities. Reciprocity describes the mutual benefit to both researchers and participants that results from effective community-based research.…”
Section: Discussionmentioning
confidence: 82%
“…This decision was informed by the recognition of the diverse roles caregivers play in supporting children with CP, including grandparents and fathers, whose perspectives are often under-represented in disability research, particularly in the South African context. 9 10 By intentionally including multiple caregivers, such as grandmothers and fathers, the study aimed to address this limitation and capture a more diverse range of experiences. Therefore, following the initial caregiver interview, participants were asked if any other family caregiver would like to participate in the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…В качестве показателей успешности данного сотрудничества следует рассмотреть такие параметры как: положительная динамика развития ребенка; положительная динамика развития самих родителей и семейных отношений, качество жизни семьи, удовлетворенность родителей; включенность членов семьи в различные социальные активности и деятельность тематических социальных групп; уровень сотрудничества родителей и профессионалов; динамика повышения родительской компетентности в вопросах обучения и воспитания детей с ОВЗ [27]. Семья может рассматриваться не только как фактор благоприятного развития, но и как потенциальный вред, если семья игнорирует предлагаемые стратегии сопровождения и не ориентируется в теории и практике комплексной помощи лицам с ОВЗ и инвалидностью [28]. Деятельностный аспект реализации инклюзивного потенциала семьи будет раскрываться через понимание того, что именно, как и с каким уровнем систематичности и результативности делает семья для успешного развития, социализации и интеграции ребенка с ОВЗ в различные социокультурные пространства и сферы [29].…”
Section: результаты исследованияunclassified
“…Как подчеркивают российские [12] и зарубежные ученые [28], существует необходимость проработки ключевых дефиниций и выравнивания терминологического поля, изначально сформированного на пересечении различных областей научных знаний [29]. На основе дифференциации терминологического ряда обсуждаемой проблемы в исследовании было сформулировано и обосновано авторское определение понятия «инклюзивный потенциал семей, воспитывающих детей ОВЗ», позволяющего подчеркнуть принципиальность синтеза внешних и внутренних ресурсов, и сместить акценты на функциональную роль семьи и аспекты родительской эффективности в процессах образовательной и социальной инклюзии.…”
Section: обсуждение результатовunclassified